Pelargonium pseudosetulosum (Geraniaceae), a new species in sect. Pelargonium from the Kogelberg-Kleinmond area in Western Cape Province, South Africa - Le Roux, M. Marianne; Manning, John C. (Phytotaxa, 2022)
Populations of plants from around Kleinmond in the Western Cape Province (South Africa), previously identified as Pelargonium setulosum, differ from typical populations of that species in ecology, distribution, and morphologically in the shape of the nectar guides, and appear to constitute a separate species. Field work was done, specimens were collected in the field, and material from four different herbaria were studied to record morphological variation. The Kleinmond populations previously included in P. setulosum are described as the new species P. pseudosetulosum. Morphological, ecological, and geographical evidence indicate that this species forms part of Pelargonium subg. Pelargonium sect. Pelargonium.